Intentionality and “free-will” from a neurodevelopmental perspective - Leisman, Gerry; Macahdo, Calixto; Melillo, Robert; Mualem, Raed (Frontiers in Integrative Neuroscience, 2012)
The nature of free-will as a subset of intentionality and probabilistic and deterministic function is explored with the indications being that human behavior is highly predictable which in turn, should compromise the notion of free-will. Data supports the notion that age relates to the ability to progressively effectively establish goals performed by fixed action patterns and that these FAPs produce outcomes that in turn modify choices (free-will) for which FAPs need to be employed. Early goals require behaviors that require greater automation in terms of FAPs that lead to goals being achieved or not; if not, then one can change behavior and that in turn is free-will. Goals change with age based on experience which is similar to the way in which movement functions. We hypothesize that human prefrontal cortex development was a natural expansion of the evolutionarily earlier developed areas of the frontal lobe and that goal-directed movements and behavior, including choice and free-will, provided for an expansion of those areas. The same regions of the human central nervous system that were already employed for better control, coordination, and timing of movements, expanded in parallel with the frontal cortex. The initial focus of the frontal lobes was the control of motor activity, but as the movements became more goal-directed, greater cognitive control over movement was necessitated leading to voluntary control of FAPs or free-will. The paper reviews the neurobiology, neurohistology, and electrophysiology of brain connectivities developmentally, along with the development of those brain functions linked to decision-making from a developmental viewpoint. The paper reviews the neurological development of the frontal lobes and inter-regional brain connectivities in the context of optimization of communication systems within the brain and nervous system and its relation to free-will.